2020
DOI: 10.3390/ma13204546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corrosion on the Natural and Whirl Frequencies of a Functionally Graded Rotor-Bearing System Subjected to Thermal Gradients

Abstract: Corrosion causes a loss of material resulting in the reduction of mass and stiffness of a component, which consequently affects the dynamic characteristics of any system. Fundamental frequency analysis of a corroded functionally graded (FG) rotor system, using the finite element method based on the Timoshenko beam theory, was investigated in the present paper. The functionally graded shaft consisting of an inner metallic core and an outer ceramic layer was considered with the radial gradation of material prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The variables š‘„ and š‘¦ are eliminated from the equilibrium condition equations of the planes (x,s) and (y,s) given in Equations ( 12), ( 13), ( 18) and (19), respectively. The resultant equations are combined by introducing a complex variable šœƒ = šœƒ š‘¦ āˆ’ š‘–šœƒ š‘„ , to obtain the governing equation for the Timoshenko FG rotor element in terms of bending slope Īø as: In (x, s) plane:…”
Section: Governing Differential Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables š‘„ and š‘¦ are eliminated from the equilibrium condition equations of the planes (x,s) and (y,s) given in Equations ( 12), ( 13), ( 18) and (19), respectively. The resultant equations are combined by introducing a complex variable šœƒ = šœƒ š‘¦ āˆ’ š‘–šœƒ š‘„ , to obtain the governing equation for the Timoshenko FG rotor element in terms of bending slope Īø as: In (x, s) plane:…”
Section: Governing Differential Equations Of Motionmentioning
confidence: 99%
“…The free vibration analysis of the FG rotor bearing system having hysteresis and viscous damping effects has been carried out in refs [15,16] using FEM. The free vibration behavior of thermally loaded FG rotor-bearing systems having defects, such as transverse crack [17], porosities [18] and corrosion defect [19] have been investigated, and the influence of these defects on the natural and whirl frequencies has been studied in detail in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above applications, the FGMs are widely used in various industries [269,270]: industrial tools such as cutting tools, heat-resistant coatings, abrasion, corrosion, but also in other fields [271][272][273][274][275][276][277][278][279][280][281][282][283][284][285][286][287][288]. Tian et al [289] investigated the thermal and mechanical shock resistances of a newly developed Si 3 N 4 /(W,Ti)C graded ceramic tool material using the water quenching methods and intermittent cutting test, respectively.…”
Section: Manufacturingmentioning
confidence: 99%
“…A vibration analysis of an FG rotor-bearing system whose FG shaft had a transverse crack and a surface crack was performed using finite element formulation [27,28]. Sathujoda et al [37] investigated the natural and whirl frequencies of a corroded FG rotor-bearing system using the finite element method (FEM). Even though a few works on the natural frequency analysis of cracked and corroded FG rotor systems are available [27,28,37] in the literature, to the best of the authors' knowledge, research on the dynamic analysis of a porous FG rotor system is rarely found.…”
Section: Introductionmentioning
confidence: 99%
“…Sathujoda et al [37] investigated the natural and whirl frequencies of a corroded FG rotor-bearing system using the finite element method (FEM). Even though a few works on the natural frequency analysis of cracked and corroded FG rotor systems are available [27,28,37] in the literature, to the best of the authors' knowledge, research on the dynamic analysis of a porous FG rotor system is rarely found. Recently, an attempt was made by Bose and Sathujoda [38] to analyse the natural frequencies of a porous FG rotor-bearing system without thermal effects using ANSYS three-dimensional finite elements.…”
Section: Introductionmentioning
confidence: 99%